(untitled) (Fiep Bulletin - online, 2011)
Goal: Verifying the theoretical possibility that the learning of a motor skill may come from the observation of other practitioners and be intensified due to the protocol of sensitization of cortical waves via cortical stimulation. Methods: The sample involves fifteen children, both male and female, aged four to five years old, divided randomly into three groups. That practiced a motor training which was according to the mirror-neuron theory. To verify the possible alterations in the cortical standard, the electroencephalogram was done (pre and post tests) and the motor performance of the groups was observed. The data were analyzed through the descriptive statistics (average and standard deviation) and studied by using statistical instruments in the inferential model through the analyses of variance of parametric type (Anova) and non-parametric type (Kruskall Wallis). Results: It was observed that in the Acquisition and Transference Phase, the group obtained improvement in the motor performance due to the decrease of absolute mistakes average and balance in the cortical waves. The values obtained were not significant. Conclusion: The hypothesis that was investigated in the mirror-neuron approach, associated with the cortical stimulation, demonstrated increase in the global performance of the group, improving the development, the agility and the skilled-motor capacity.